Caracterización de los principales parásitos gastrointestinales provenientes de heces de caninos colectadas en parques de la comuna 3 Popayán (2022)
This document established that if good management of feces is not carried out, both in the community that owns pets and the community in general, it will generate a great problem for both animal health and public health, for what which will be carried out an analysis through the flotation test for the detection of parasitic eggs in parks of the commune three of Popayán among which are: Aida Lucia Park, North Palace Park, Palace Park and Yanaconas Park with which a general perception of said problem. This study will contribute in a robust way to the possible modification of waste management, against which it is clear that a complex path is expected that will require time and effort for the awareness of the community in general but that will certainly add improvements in public health .